(untitled) (Cyberspace: Jurnal Pendidikan Teknologi Informasi, 2021)
Virtual Private Network (VPN) is a technology that offers low-cost remote access solutions for companies. The IPSec protocol provides cryptography services and network security for data transmission. Generic Routing Encapsulation (GRE) tunnel exists to encapsulate multicast and broadcast packets into unicast packets. This is very usable which IPSec does not support encryption of multicast and broadcast packets. The target of this simulation is that Router 1 shows that the network is protected by GRE. The first thing to do is set the network topology. Here, for example, there are two offices that want to transmit data to each other. Each of these offices has a switch, FTP server, DNS server, router, and PC. Then set the IP address of each device and connect it with cables. Router 2 and Router 3 function to connect the two offices in one WAN network. Each of these data transmissions is IPSec protected for data encryption protection then GRE coated for transmission encapsulation. From simulation results, we can conclude that both network can be connected and communicated each other with protection from GRE tunnel.